Facile preparation of self-assembled high-performance cellulose based composite. (12th April 2022) - Yan, Ming; Lu, Hailong; Wu, Ting; Zhang, Lili; Ma, Jinxia; Zhou, Xiaofan
Abstract: The huge accumulation of plastic wastes is emerging as a serious threat to the ecological environment and human health. Herein, inspired by the reinforcement principle of lignin-carbohydrate complexes (LCC) in the natural trees, we design a green, highly efficient, and eco-friendly method to prepare cellulose composites with excellent performances. Cationic Guar Gum (CGG) and Lignosulfonate (LS), which are derived from biomass, are employed as raw materials to form LS-CGG complexes (LGC) acted as LCC analogs to improve the performance of the cellulose framework. Based on the principle of electrostatic interactions, a self-assembled and facile infiltrated strategy has been applied in the preparation of the LGC-filter paper complex (LGC-FP), which can be industrial-scale manufactured employing established and mature processes from pulping and papermaking industry. This work provides an eco-friendly, low-cost, and scalable route to prepare bioplastics, which is a promising alternative to address the "white pollution" and reach the carbon neutrality goal to a certain extent. Graphical abstract: Image 1